2021
DOI: 10.1021/acs.macromol.1c00437
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Orientational Genesis on the Actuation of Monodomain Liquid Crystalline Elastomers

Abstract: The macroscopic alignment of the nematic director within liquid crystalline elastomers (LCEs) amplifies the magnitude of the directional strain response. Theory predicts that the stimuli response of LCEs will be affected by the orientational genesis of cross-linking. We examine compositionally identical LCEs aligned by either mechanical or surface techniques. The two-step procedure to prepare LCEs by mechanical alignment first forms cross-links in a disordered state (e.g., isotropic orientational genesis), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…To be noted that the final properties of the LCNs are strictly dependent on both monomer composition and polymerization conditions, e.g. the temperature set during irradiation can modify the macroscopic properties of the films (Hebner et al, 2021) The materials tested in this study are called LCNx, where x (=10, 20 or 40) represent the % mol/mol of the cross-linker (RM257) present in the formulation. Increasing the amount of RM257 leads to a higher ll OPEN…”
Section: Scaffold Preparation and Characterizationmentioning
confidence: 99%
“…To be noted that the final properties of the LCNs are strictly dependent on both monomer composition and polymerization conditions, e.g. the temperature set during irradiation can modify the macroscopic properties of the films (Hebner et al, 2021) The materials tested in this study are called LCNx, where x (=10, 20 or 40) represent the % mol/mol of the cross-linker (RM257) present in the formulation. Increasing the amount of RM257 leads to a higher ll OPEN…”
Section: Scaffold Preparation and Characterizationmentioning
confidence: 99%
“…Liquid crystal elastomers (LCEs) capitalize on the interplay between the self-association of LC functional groups and the entropic conformation of polymer backbones, resulting in phase-dependent macroscopic shape deformations. Past studies have shown that LCEs are capable of exhibiting a rich palette of reversible and well-programed anisotropic shape changes in response to a wide range of external stimuli, including heat, , solvents, light, and magnetic , and electric fields and have attracted great interest for their potential in the design and synthesis of responsive biomedical devices, soft actuators, robotics, and active surface structures. LC moieties can be incorporated into polymer chains as either part of the polymer backbone (main-chain LCE) or the pendant functional group (side-chain LCE). Previous studies have shown that in LC phases, the conformation of LC polymer chains can deviate from statistically spherical random coils, depending on the configuration of the pendant LC functional groups, as seen in Figure . ,, For prolate LC polymers, polymer backbones align along the orientation of the mesogenic groups (called the director), resulting in a longer radius of gyration parallel to the LC director ( R ∥ ) than that perpendicular to the LC director ( R ⊥ ).…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to mesogen-mesogen interactions present in the nematic phase during crosslinking. 23,24 While these studies demonstrated that the T NI is dependent on a number of network properties and synthesis conditions, we lack a comprehensive understanding of how T NI varies in LCEs and how to predict changes in T NI for specific changes in network structure and chemistry.…”
Section: Introductionmentioning
confidence: 99%